Dinamika Pembaharuan Pendidikan Islam: Studi Peran Nahdlatul Ulama di Indonesia - Aslam Raf’ha; Hasriana Hasriana; Idrus L (Jurnal Sosial Humaniora dan Pendidikan, 2026)
This study examines the dynamics of Islamic educational reform in the context of the role of Nahdlatul Ulama in Indonesia through a qualitative approach based on a literature review. The focus of the study is on the integration of Ahlussunnah wal Jama’ah values into the curriculum, institutional transformation in education, and contributions to religious moderation and deradicalization. The analysis indicates that curriculum reform is achieved by integrating pesantren traditions with modern pedagogical approaches that emphasize digital literacy and critical thinking skills. In terms of institutional aspects, decentralization creates space for local innovation, thereby strengthening governance effectiveness and expanding access to education. The role in religious moderation is realized through the internalization of tolerance values, the strengthening of socio-political literacy, and the utilization of social networks and digital technology. The research findings indicate that the renewal of Islamic education within the NU context is adaptive, integrative, and contextual in response to social and global changes. The contribution of this research lies in strengthening an analytical framework that connects the dimensions of curriculum, institutional structure, and religious moderation into a single dynamic unit of contemporary Islamic education.